ANALISIS HUKUM FATWA DSN-MUI TENTANG AQAD QARD AL-HASAN PADA PEMBIAYAAN USAHA MIKRO KECIL MENENGAH UMKM DI KECAMATAN CIBIRU KOTA BANDUNG - Azka Hijrotul Falah; Arifin Ilham; Jaenudin Jaenudin; Dian Herdiana (CV. Denasya Smart Publisher, 2025)
Al-Qardh al-Hasan is a loan agreement (tabarru’) that functions as a social instrument in Islamic Financial Institutions (LKS) to help customers in need, especially Micro, Small, and Medium Enterprises (MSMEs). This study aims to align the application of the Qard al-Hasan agreement in MSME financing in the Cibiru area with the provisions of the DSN-MUI Fatwa No. 19/DSN-MUI/IV/2001 concerning Al-Qardh. The research method used is normative-empirical law with a regulatory approach (statutory approach) and a contextual approach (conceptual approach), and supported by field data (field research). The results of the study indicate that the application of the Qard al-Hasan agreement by BMD serving MSMEs in Cibiru has generally complied with sharia provisions, especially regarding the prohibition on requiring additional imbalances from the loan principal (the principle of kullu qardin jarra manfa’atan fahuwa riba).